Judicial Review of Labour Arbitration in Ontario - Thompson, Mark (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
Courts in Ontario have been increasingly willing to quash grievance arbitration awards. This article analyses the services of this conflict between the judiciary and arbitrators, the role the courts have assumed because of the compulsory use of arbitration, and the judges' reliance on precedent established British commercial arbitration. Most Ontario cases have involved one of four issues — evidence of intent, procedural violations of grievance clauses, disciplinary penalties, and denial of natural justice. In the first three areas especially, the courts have favoured narrow interpretations of collective agreements, limiting arbitrators' jurisdiction. This problem illustrates the difficulty in attempting to legislate a complex institution like grievance arbitration based on foreign experience, i.e. the United States.